2012
DOI: 10.1371/journal.pgen.1002483
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic Restructuring in the Tasmanian Devil Facial Tumour: Chromosome Painting and Gene Mapping Provide Clues to Evolution of a Transmissible Tumour

Abstract: Devil facial tumour disease (DFTD) is a fatal, transmissible malignancy that threatens the world's largest marsupial carnivore, the Tasmanian devil, with extinction. First recognised in 1996, DFTD has had a catastrophic effect on wild devil numbers, and intense research efforts to understand and contain the disease have since demonstrated that the tumour is a clonal cell line transmitted by allograft. We used chromosome painting and gene mapping to deconstruct the DFTD karyotype and determine the chromosome an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
166
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(175 citation statements)
references
References 39 publications
9
166
0
Order By: Relevance
“…Despite the absence of cytogenetically identifiable sex chromosomes in DFT1, studies using fluorescence in situ hybridization and DNA sequencing have found evidence for two X chromosome copies in DFT1 (13,14). Furthermore, the number of single point substitution variants mapping to the X chromosome in DFT1 suggested that the two X chromosomes were germ-line homologs rather than recent somatic duplicates (13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the absence of cytogenetically identifiable sex chromosomes in DFT1, studies using fluorescence in situ hybridization and DNA sequencing have found evidence for two X chromosome copies in DFT1 (13,14). Furthermore, the number of single point substitution variants mapping to the X chromosome in DFT1 suggested that the two X chromosomes were germ-line homologs rather than recent somatic duplicates (13).…”
Section: Resultsmentioning
confidence: 99%
“…The DFTD clone has been closely monitored during its epidemic sweep through Tasmania ( Fig. 1A) (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…A devil fibroblast cell line (18) was used as a control. Three cell lines derived from DFTD primary tumors (1426, 4906 and C5065) are described (33,34). Complete medium and cell culture conditions are described in SI Appendix.…”
Section: Methodsmentioning
confidence: 99%
“…Despite no sex chromosomes being in any sample being analyzed, duplicates of 11/14 Xchromosome genes were found scattered amongst the marker chromosomes, suggesting positive selection for these X-chromosome genes [40,41]. Fluorescence hybridization confirmed these findings, and in addition found traces of male genes, suggesting the ancestral donor was female.…”
mentioning
confidence: 66%
“…Fluorescence hybridization confirmed these findings, and in addition found traces of male genes, suggesting the ancestral donor was female. This was supported by both the absence of Y chromosome hybridization and the lack of SRY sequence in DFTD tumors [40,41].…”
mentioning
confidence: 77%